7-4x=6x-23

Simple and best practice solution for 7-4x=6x-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-4x=6x-23 equation:


Simplifying
7 + -4x = 6x + -23

Reorder the terms:
7 + -4x = -23 + 6x

Solving
7 + -4x = -23 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
7 + -4x + -6x = -23 + 6x + -6x

Combine like terms: -4x + -6x = -10x
7 + -10x = -23 + 6x + -6x

Combine like terms: 6x + -6x = 0
7 + -10x = -23 + 0
7 + -10x = -23

Add '-7' to each side of the equation.
7 + -7 + -10x = -23 + -7

Combine like terms: 7 + -7 = 0
0 + -10x = -23 + -7
-10x = -23 + -7

Combine like terms: -23 + -7 = -30
-10x = -30

Divide each side by '-10'.
x = 3

Simplifying
x = 3

See similar equations:

| -7x+3x+9=-3 | | -35=-3x+5+5x | | -7+3x+9=-3 | | m^4+m^2n^2+n^4=0 | | 7(8/5) | | a^2-b^2-10a+25= | | 8/5(7) | | 4x-3x-10=-2 | | (x^3)+6(x^2)+11x+6=0 | | x+2+x+x=6-3 | | F(x)=4x-9-x^3 | | 7k+6=69 | | 4-7(3x-1)=-4x+28 | | 127=(16*59.3/x)(16*9.9/x) | | p-8=-15/p | | -6x+7+7x=9 | | x-sqrt(11-10x)=-22 | | 10xwhat=990 | | 4x+6=4+3x | | 5t-9=31 | | 7k-5=30 | | 6a-5=43 | | -30-6a=2(1-7a) | | 7a^2-24a-4=0 | | 31+6n=-5(1-3n) | | 4(2)-3/2(1)-1 | | 2x+26=0 | | -9+2x+4x=9 | | 5x-6x-3=-5 | | 6+4(3-2n)=-4n+14 | | 1/6=1.5x | | 8y=-3x+4 |

Equations solver categories